ASSESSMENT AND EVALUATION IN ENGLISH LANGUAGE TEACHING - Djoldasova, G. (SCIENCE and SOCIETY, 2025)
An essential part of teaching and learning English as a foreign language (EFL) is assessment and evaluation. This article examines how assessment and evaluation are integrated into EFL classes, highlighting how crucial they are for gauging student progress, directing instruction, and improving the caliber of instruction.